Computational classification of core and outer fucosylation of N‐glycoproteins in human plasma using collision‐induced dissociation in mass spectrometry. (23rd September 2020) - Jeong, Hoi Keun; Hwang, Heeyoun; Kang, Young‐Mook; Lee, Hyun Kyoung; Park, Gun Wook; Lee, Ju Yeon; Kim, Dong Geun; Lee, Ji Won; Lee, Sang Yoon; An, Hyun Joo; Kim, Jin Young; Yoo, Jong Shin
Abstract : Rationale: Glycoprotein fucosylation, one of the major posttranslational modifications, is known to be highly involved in proteins related to various cancers. Fucosylation occurs in the core and/or outer sites of N‐glycopeptides. Elucidation of the fucosylation type of N‐glycoproteins is therefore important. However, it has remained a challenge to classify the fucosylation types of N‐glycopeptides using collision‐induced dissociation (CID) tandem mass (MS/MS) spectra. Methods: The relative intensities of the Y1 F, Y2 F, Y3 F, and Y4 F product ions in the CID‐MS/MS spectra of the IgG N‐glycopeptides were measured for core fucosylation. The Core Fucose Index (CFI) was then calculated by multiplication of the relative intensities with a weight factor from logistic regression to differentiate between the core and none fucosylation. From the relative intensities of the B2 F and B3 SF ions of the MS/MS spectra of the AGP N‐glycopeptides for outer fucosylation, the Outer Fucose Index (OFI) was calculated to differentiate between the outer and none fucosylation. Results: In order to classify core and/or outer fucosylation of N‐glycoproteins, we defined the fucosylation score (F‐score) by a sigmoidal equation using a combination of the CFI and the OFI. For application, we classified the fucosylation types of N‐glycoproteins in human plasma with 99.7% accuracy from the F‐score. Human plasma samples showed 54.4%, 33.3%, 10.3%, and 1.6% for none, core, outer, and dual fucosylated N‐glycopeptides, respectively. Core fucosylation was abundant at mono‐ and bi‐antennary N‐glycopeptides. Outer fucosylation was abundant at tri‐ and tetra‐antennary N‐glycopeptides. In total, 113 N‐glycopeptides of 29 glycoproteins from 3365 glycopeptide spectral matches (GPSMs) were classified for different types of fucosylation. Conclusions: We established an F‐score to classify three different fucosylation types: core, outer, and dual types of N‐glycopeptides. The fucosylation types of 20 new N‐glycopeptides from 11 glycoproteins in human plasma were classified using the F‐score. Therefore, the F‐score can be useful for the automatic classification of different types of fucosylation in N‐glycoproteins of biological fluids including plasma, serum, and urine.